Single center evidence for the treatment of basal cell carcinoma of the head and neck - Bertozzi, Nicolò; Simonacci, Francesco; Greco, Michele Pio; Grignaffini, Eugenio; Raposio, Edoardo (Acta Biomedica Atenei Parmensis, 2019)
Aim: Basal Cell Carcinoma (BCC) alone accounts for 80% of cases of non-melanoma skin cancer (NMSC), which characteristically develops on sun-exposed skin. Indeed the most common site of BCC is the head and neck region (80%). The purpose of this study to review the experience of our center with BCC in the head and neck region to report the sites of occurrence and treatment. Materials and method: We retrospectively reviewed 77 patients with BCC of the head and neck, who revived surgical treatment within our plastic surgery division. Basic demographic data, cancer site and size, surgical treatment and histological data were collected. The mean follow-up period was 12 months. Results: The study population included 37 males and 40 females, with a mean age of 74.12 years. The nasal unit was the main site of BCC (31.82%), followed by the periorbital (13.64%) and cervical (12.5%) units. Primary closure was the main surgical procedure performed (72.5%), followed by local flap (26.1%) and full-thickness skin grafts (1.4%). The safety resection margin ranged from 4.5 to 9 mm, with a 98.7% complete removal rate. Neither recurrence nor any newly-developed lesions were reported during follow-up in any patient. Discussion: Our work reflects the shift in the incidence of BCC, which now seems to be more frequent in females. Furthermore, our data strengthens the association between UVR exposure and BCC, confirms its predilection to occur on the nasal unit and validates surgical excision as the gold standard treatment for skin cancer.